The Role of Financial Technology in Corporate Financial Management - Nurul Masithoh (Universitas Muhammadiyah Palu, 2022)
The rapid advancement of digital technology over the past decade has significantly influenced various sectors, particularly in business and finance. One of the most impactful innovations is the emergence of Financial Technology (FinTech), which integrates digital technology with financial services to enhance efficiency, transparency, and accuracy in financial management. In Indonesia, FinTech has experienced substantial growth and is being utilized by companies of all sizes small, medium, and large to support their financial operations. This article explores the role of FinTech in strengthening corporate financial management, focusing on the use of digital payment systems, cloud-based accounting, automated cash flow management, and AI-driven financial analytics. This study employs a qualitative descriptive method, drawing on literature reviews and case studies from selected Indonesian companies that have implemented FinTech solutions. The findings indicate that FinTech adoption facilitates corporate digital transformation, improves operational efficiency, reduces human error, and supports real-time data-based financial decision-making. Nevertheless, challenges such as data security, human resource readiness, and regulatory compliance must still be addressed. These insights aim to inform business stakeholders about the urgency and strategic approaches for integrating FinTech into corporate financial systems.